Poligami dan gender dalam Tok Guru karya Shahnon Ahmad dan Pujangga Melayu karya Mohd. Affandi Hassan. - Mohd. Zariat Abdul Rani, (Universiti Kebangsaan Malaysia, 2008)
In Islam, justice is the ultimate value in the understanding of ethics and morality. This valuation is evident in polygamy, as justice is the most important prerequisite in the understanding and application of the practice. The onset of modernity, however, has seen polygamy engender various forms of disputation, especially among modem feminists who by and large assume the practice to be one that perpetuates gender inequality and injustice. This in turn give rise to paradoxical perceptions, because on the one hand, Islam is said to be a religion that patently espouses justice; but on the other, Islam is seen as perpetuating a marriage practise (polygamy) that seemingly benefits one gender at the expense of the other. It is in this context that this article explores the above paradox with reference to Malay novels. This article aims to detail perceptions on polygamy of Malay novelists, as well as to explore how gender issues in the context of polygamy are presented within their works. Two novels will be analysed: Tok Guru (1988) by Shahnon Ahmad and Pujangga Melayu (1998) by Mohd. Affandi Hassan. Beside the fact that these novels have attained privileged status within the Malay literary world, they are pertinent to this study more because of their respective treatments of polygamy and gender issues. Analysis indicates that each novel proposes a different outlook and approach to deal with the issue of polygamy and gender. It is interesting to note that these differences will help to extend the debate on the issues of polygamy and gender.